A novel framework for integrating data mining with control loop performance assessment. Issue 1 (30th September 2015) - Das, Laya; Srinivasan, Babji; Rengaswamy, Raghunathan
Abstract : Data driven control loop performance assessment techniques assume that the data being analyzed correspond to single plant‐controller configuration. However, in an industrial setting where processes are affected due to the presence of feedstock variability and drifts, the plant‐controller configuration changes with time. Also, user‐defined benchmarking of control loops (common in industrial plants) requires that the data corresponding to optimal operation of the controller be known. However, such information might not be available beforehand in which case it is necessary to extract the same from routine plant operating data. A technique that addresses these fundamental requirements for ensuring reliable performance assessment is proposed. The proposed technique performs a recursive binary segmentation of the data and makes use of the fact that changes in controller settings translate to variations in plant output for identifying regions corresponding to single plant‐controller configurations. The statistical properties of the data in each such window are then compared with the theoretically expected behavior to extract the data corresponding to optimal configuration. This approach has been applied on: (1) raw plant output, (2) Hurst exponent, and (3) minimum variance index of the process data. Simulation examples demonstrate the applicability of proposed approach in industrial settings. A comparison of the three routes is provided with regard to the amount of data needed and the efficacy achieved. Key results are emphasized and a framework for applying this technique is described. This tool is of significance to industries interested in an automated analysis of large scale control loop data for multiple process variables that is otherwise left unutilized. © 2015 American Institute of Chemical Engineers AIChE J, 62: 146–165, 2016